The pollen receptor kinase LePRK2 mediates growth-promoting signals and positively regulates pollen germination and tube growth - Zhang, D. (2008)
In flowering plants, the process of pollen germination and tube growth is required for successful fertilization. A pollen receptor kinase from tomato (Solanum lycopersicum), LePRK2, has been implicated in signaling during pollen germination and tube growth as well as in mediating pollen (tube)-pistil communication. Here we show that reduced expression of LePRK2 affects four aspects of pollen germination and tube growth. First, the percentage of pollen that germinates is reduced, and the time window for competence to germinate is also shorter. Second, the pollen tube growth rate is reduced both in vitro and in the pistil. Third, tip-localized superoxide production by pollen tubes cannot be increased by exogenous calcium ions. Fourth, pollen tubes have defects in responses to style extract component (STIL), an extracellular growth-promoting signal from the pistil. Pollen tubes transiently overexpressing LePRK2-fluorescent protein fusions had slightly wider tips, whereas pollen tubes coexpressing LePRK2 and its cytoplasmic partner protein KPP (a Rop-GEF) had much wider tips. Together these results show that LePRK2 positively regulates pollen germination and tube growth and is involved in transducing responses to extracellular growth-promoting signals. © 2008 American Society of Plant Biologists.